Re-description of Oxynoemacheilus longipinnis from the Persian Gulf basin (Teleostei: Nemacheilidae). Issue 3 (3rd July 2017) - Sayyadzadeh, Golnaz; Esmaeili, Hamid Reza; Eagderi, Soheil; Jouladeh-Roudbar, Arash; Masoudi, Mojtaba; Vatandoust, Saber
Abstract : The monotypic nemacheilid loach genus Ilamnemacheilus was erected based on morphological features of a single individual described as Ilamnemacheilus longipinnis Coad and Nalbant, 2005 from the Tigris River tributary in Iran. It was later transferred to the genus Oxynoemacheilus based on molecular and morphological studies without a description. Here, we re-describe O. longipinnis based on additional specimens collected from near the type locality. It is distinguished from the other oxynoemacheilid loaches of the Tigris River by having a suborbital groove in males, the number of the dorsal-fin rays, the colouration pattern of the body, and the shape of the upper lip and the caudal fin.